2011
DOI: 10.2337/dc10-2456
|View full text |Cite
|
Sign up to set email alerts
|

Primary Dietary Intervention Study to Reduce the Risk of Islet Autoimmunity in Children at Increased Risk for Type 1 Diabetes

Abstract: OBJECTIVETo determine whether delaying the introduction of gluten in infants with a genetic risk of islet autoimmunity is feasible, safe, and may reduce the risk of type 1 diabetes–associated islet autoimmunity.RESEARCH DESIGN AND METHODSA total of 150 infants with a first-degree family history of type 1 diabetes and a risk HLA genotype were randomly assigned to a first gluten exposure at age 6 months (control group) or 12 months (late-exposure group) and were followed 3 monthly until the age of 3 years and ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
163
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 20 publications
1
163
0
4
Order By: Relevance
“…Study population Data from two ongoing German birth cohorts of individuals with a family history of type 1 diabetes born between 1989 and 2000 (BABYDIAB [7]) and between 2000 and 2006 (BABYDIET [8]) were combined for this analysis. Both studies aimed to prospectively examine the natural history of islet autoimmunity and type 1 diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study population Data from two ongoing German birth cohorts of individuals with a family history of type 1 diabetes born between 1989 and 2000 (BABYDIAB [7]) and between 2000 and 2006 (BABYDIET [8]) were combined for this analysis. Both studies aimed to prospectively examine the natural history of islet autoimmunity and type 1 diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…A subgroup of 150 children carrying high-risk HLA genotypes participated in the BABYDIET gluten intervention study (ClinicalTrials.gov NCT01115621) to investigate whether delay of exposure to gluten could reduce the risk of developing autoantibodies. The intervention failed to show an effect on islet autoantibody development and all participants continued with follow-up examinations according to the natural history protocol [8]. Detailed descriptions of the design of each study have been reported [7,8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of this, they hypothesized that GFD may prevent the occurrence of other autoimmune diseases. However, subsequent studies have not confirmed the protective role of GFD [18,19]. Development of other autoimmune disease is more likely if the CD is diagnosed in young individuals with positive family history of CD [20].…”
Section: Celiac Disease and Other Autoimmune Diseasesmentioning
confidence: 99%
“…This knowledge is important for the design of screening and re-screening strategies. Here we analysed the prospectively followed German BABYDIAB/BABYDIET birth cohort [2,5] to address this.…”
mentioning
confidence: 99%